2007
DOI: 10.1242/dev.02722
|View full text |Cite
|
Sign up to set email alerts
|

Gene replacement reveals a specific role for E-cadherin in the formation of a functional trophectoderm

Abstract: During mammalian embryogenesis the trophectoderm represents the first epithelial structure formed. The cell adhesion molecule E-cadherin is ultimately necessary for the transition from compacted morula to the formation of the blastocyst to ensure correct establishment of adhesion junctions in the trophectoderm. Here, we analyzed to what extent E-cadherin confers unique adhesion and signaling properties in trophectoderm formation in vivo. Using a gene replacement approach, we introduced N-cadherin cDNA into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 63 publications
5
116
0
3
Order By: Relevance
“…Consistent with this, biophysical studies demonstrated that E-cadherin mediates stronger bonds at the molecular level than any other cadherins (Dufour et al, 1999;Chu et al, 2006;Panorchan et al, 2006). Moreover, although E-cadherin and N-cadherin may transiently coexist in certain cells, they are generally mutually exclusive, and studies on epithelial cell lines or in mouse and Xenopus embryos in which E-and N-cadherins have been interchanged clearly indicate that they can only partially substitute each other (Luo et al, 2001;Kan et al, 2007;Wheelock et al, 2008;Nandadasa et al, 2009;Libusova et al, 2010).…”
Section: Introductionmentioning
confidence: 91%
“…Consistent with this, biophysical studies demonstrated that E-cadherin mediates stronger bonds at the molecular level than any other cadherins (Dufour et al, 1999;Chu et al, 2006;Panorchan et al, 2006). Moreover, although E-cadherin and N-cadherin may transiently coexist in certain cells, they are generally mutually exclusive, and studies on epithelial cell lines or in mouse and Xenopus embryos in which E-and N-cadherins have been interchanged clearly indicate that they can only partially substitute each other (Luo et al, 2001;Kan et al, 2007;Wheelock et al, 2008;Nandadasa et al, 2009;Libusova et al, 2010).…”
Section: Introductionmentioning
confidence: 91%
“…) were unable to form a functional blastocyst, indicating a specific requirement for Cdh1 during trophectoderm formation that Cdh2 cannot supply (Kan et al, 2007).…”
Section: Cdh2/cdh2mentioning
confidence: 99%
“…Because the gene replacement of Cdh1 with Cdh2 resulted in a trophectoderm defect at E3.5 (Kan et al, 2007), we focused on the preimplantation development of embryos from heterozygous Cdh1 HA/þ intercrosses. In vivo and in vitro morulae of Cdh1 HA/HA embryos compact and form proper blastocysts similar to their littermates as shown by time-lapse recording (Supp.…”
Section: Knock-in Allele Confers Proper Embryogenesis and Tissue Intementioning
confidence: 99%
See 2 more Smart Citations